2005
DOI: 10.1200/jco.2005.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Weight, Weight Gain, and Survival After Breast Cancer Diagnosis

Abstract: Weight and weight gain were related to higher rates of breast cancer recurrence and mortality, but associations were most apparent in never-smoking women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
446
2
18

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 595 publications
(484 citation statements)
references
References 51 publications
18
446
2
18
Order By: Relevance
“…The largest study to date was from the Nurse's Health Study Cohort (NHS), in which self-reported body weight measures were obtained in a subsample of over 5000 generally healthy women who were subsequently diagnosed with breast cancer and followed for a median of 9 years. An intriguing finding from this study [24] was that a gain in BMI post-diagnosis was related negatively to prognosis in women who reported never smoking but not in the women who reported ever smoking. The current report investigates the specific effects of post diagnosis weight change on breast cancer recurrence using data collected from two large studies of breast cancer survivors.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…The largest study to date was from the Nurse's Health Study Cohort (NHS), in which self-reported body weight measures were obtained in a subsample of over 5000 generally healthy women who were subsequently diagnosed with breast cancer and followed for a median of 9 years. An intriguing finding from this study [24] was that a gain in BMI post-diagnosis was related negatively to prognosis in women who reported never smoking but not in the women who reported ever smoking. The current report investigates the specific effects of post diagnosis weight change on breast cancer recurrence using data collected from two large studies of breast cancer survivors.…”
Section: Introductionmentioning
confidence: 64%
“…The literature regarding post-diagnosis weight gain and prognosis [18][19][20][21][22][23][24] is not extensive and it is difficult to compare results across studies, because the studies often used different measures to evaluate prognosis. Some examined only overall survival, while others use disease-free, relapsefree or recurrence-free survival, and even among the latter three, definitions often vary across study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were especially apparent in women who never smoked, among women with earlier stage disease or those who were normal weight before diagnosis [33]. In contrast, a collaborative effort between the LACE study and the WHEL study, did not observe an association between post-diagnosis weight gain and recurrence risk in the first 5-7 years postdiagnosis [34].…”
Section: Biological Mechanismmentioning
confidence: 86%
“…Most patients diagnosed with cancer will receive treatment, and patients undergoing treatment experience a multitude of symptoms, including fatigue, pain, difficulty breathing, nausea, appetite loss, and unintentional weight change (2)(3)(4)(5). These symptoms can negatively impact one's ability to complete treatment as well as one's quality of life during and after treatment (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%